Interfacing the radiology information system to the modality: an integrated approach...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Garland HT; Cavanaugh BJ; Cecil R; Hayes BL; Lavoie S; Leontiev A; Veprauskas J (Journal of Digital Imaging)
The radiology information system (RIS) provides patient and examination information that is used in setting up and performing a radiologic procedure. In a digital imaging environment, information from the RIS can also be used to populate fields in the Digital Imaging and Communications in Medicine (DICOM) image header. Ideally, information from the RIS should be available at the modality at the time of the examination, and automatically be attached to the image in the appropriate DICOM fields before storage in the picture archiving and communications system (PACS). We have designed a highly integrated RIS interface for a digital radiography (DR) system. This interface employs browser technology to make RIS information conveniently available at the modality, and DICOM modality performed procedure step (MPPS) for RIS/DR information exchange. A novel feature of our approach is that a single display screen at the modality is used to alternatively display either the modality control window or the RIS window. Full access to RIS capabilities is available at the modality, including worklists and prior reports. Copyright (c) 1999 by W.B. Saunders Company